Postural stability in adults under 30 years of age - Goliwąs, Magdalena; Lech, Furmaniuk; Lewandowski, Jacek (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The aim of the present study is to determine the standard values of parameters describing postural stability: COP area, COP length and lower limbs loading symmetry index (SI). Material and Methods. 60 students of physiotherapy from the University School of Physical Education in Poznań participated in the study. In the case of 29 students, contraindications to participating in the study were identified. Ultimately, 31participants were selected to take 30-second tests performed while standing on both feet, with and without visual control. Results. The standard values of the COP length parameter were determined. In the test with visual control, 6.5% of participants achieved high and very high scores. 87% achieved average scores. In the test without visual control, 9.7% of participants achieved high and very high scores, while 80.6% attained average scores. The SI index had a normal distribution. It showed that most people put the weight onto their left lower limb, both with and without visual control. Conclusion. Healthy, active adults between 21-24 years of age most often bear weight on the left lower limb. The values describing postural stability were above-average
Keywords: postural control; stability; Symmetry Index; COP